Preparation of spiral porous stainless steel hollow fiber membranes by a modified phase inversion-sintering technique - Li, H.; Song, J.; Tan, X.; Jin, Y.; Liu, Shaomin (Elsevier, 2015)
The practical use of inorganic hollow fibre membranes has been limited by their brittleness. When assembled inside a membrane module for high temperature applications, the unavoidable thermal expansion or shrinkage would break the membrane. To overcome this problem, in this paper, spiral-shaped porous stainless steel (PSS) hollow fiber membranes have been developed via a modified phase inversion–sintering technique using 316 L stainless steel powder as the membrane material, polysulfone as the polymeric binder and N-methylpyrrolidone as the solvent, respectively. The effects of sintering conditions on the hollow fiber properties have been investigated extensively to optimize the preparation. In order to obtain the desired porous structure, high performance and appropriate mechanical strength, the PSS hollow fiber precursors should be calcined in O2-free sintering atmosphere between 1050 °C and 1100 °C. Under the optimal sintering conditions, the resultant PSS hollow fibre membranes have a bimodal pore size distribution of 0.1–3 μm diameter, high mechanical strength of 290–600 MPa, and the nitrogen permeances ranged between 2.23×10−4 and 2.84×10−5 mol m−2 s−1 Pa−1. When two sides are fixed by sealant, such spiral hollow fiber membranes are able to flexibly expand by 20% and shrink by at most 57% of its original length, thus suitable for variable high-temperature operations as they can offset the thermal expansion and contraction caused by the temperature change.